2001
DOI: 10.1016/s0735-1097(01)01468-1
|View full text |Cite
|
Sign up to set email alerts
|

Pause-dependent torsade de pointes following acute myocardial infarction

Abstract: Infarct-related torsade de pointes is uncommon but potentially lethal. An acquired long QT syndrome should be considered in patients recovering from MI who experience polymorphic VT as specific therapeutic measures are mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…Polymorphic VT storm in a patient with coronary disease is strongly suggestive of acute myocardial ischemia; pauses may occur prior to polymorphic VT even in the absence of QT prolongation. Pause-dependent VT with marked QT prolongation should be managed as torsades de pointes (see Section 7.5), although acute ischemia can also present in this fashion (391). Frequent appropriate ICD shocks may represent part of the natural history of advanced heart disease and may or may not portend a serious deterioration in underlying prognosis (392).…”
Section: Recommendationsmentioning
confidence: 99%
“…Polymorphic VT storm in a patient with coronary disease is strongly suggestive of acute myocardial ischemia; pauses may occur prior to polymorphic VT even in the absence of QT prolongation. Pause-dependent VT with marked QT prolongation should be managed as torsades de pointes (see Section 7.5), although acute ischemia can also present in this fashion (391). Frequent appropriate ICD shocks may represent part of the natural history of advanced heart disease and may or may not portend a serious deterioration in underlying prognosis (392).…”
Section: Recommendationsmentioning
confidence: 99%
“…68 Crotti et al reported that 2 (15%) of 13 Caucasian patients with ACS-TdP were found to carry LQTS mutations (KCNH2 R744X, SCN5A E446K) ( Table 3). 69 Additionally, 9 (82%) of the remaining 11 patients carried the KCNH2 K897T variant, which is commonly present in an allele frequency of 35% in Caucasians but is rare in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…However, one more clinical context that may be related to TdP needs to be mentioned, namely, the QT interval prolongation in acute cardiac diseases associated with large amount of stunned myocardium, ie, the reperfused myocardial infarction and the group of stress-related cardiomyopathies. 2,3 The latter covers takotsubo cardiomyopathy and transient left ventricular dysfunctions associated with intracranial events (eg, subarachnoid hemorrhage), pheochromocytoma, exogenous catecholamine administration, or severe acute illnesses (especially those treated in intensive care units). 3 In the course of these entities, deep inverted T-waves with QT interval prolongation can emerge in the first days after the index event.…”
Section: To the Editormentioning
confidence: 99%